Digitalisation of Arbitration, Cyber Security Risk and International Arbitration Centre: Some Observations - Md. Nor, Mohd Zakhiri; Mohamed, Khadijah; Md Isa @ Yusuff, Yusramizza; Mohamad, Ani Munirah (2021)
The march of digitisation and technological adoption occurs in arbitration, exposing the arbitration centre to cybersecurity risks. The purpose of this study is to investigate the arbitral rules of the Asian International Arbitration Centre ("AIAC"), the Hong Kong International Arbitration Centre ("HKIAC"), the International Chamber of Commerce ("ICC"), and the Arbitration Institute of the Stockholm Chamber of Commerce ("SCC"), as well as the application of those rules by the parties and the tribunal. This article also analyses the efforts made by AIAC, HKIAC, ICC, and SCC outside of their specific arbitral rules, notably concerning technology use and cybersecurity protections. This study used a combination of qualitative research and a comparative analytic method. This research concludes that there is no provision in the arbitral rules of these four institutions for explicit cybersecurity measures. However, the parties and the arbitral tribunal are entitled to implement suitable cybersecurity safeguards. This study also discovered that these four organisations intend to guide cybersecurity measures outside of their arbitral rules